2018
DOI: 10.21470/1678-9741-2018-0070
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Efficacy of Oral versus Intravascular Magnesium in the Prevention of Hypomagnesemia and Arrhythmia after CABG

Abstract: ObjectiveCardiac arrhythmias are a common challenge following open-heart surgeries. Hypomagnesemia is believed to be correlated with this condition. Prophylactic intravenous magnesium supplementation has been practiced for a long time in patients undergoing CABG. This study was designed in an attempt to compare the efficacy of oral versus intravenous routes in the prevention of hypomagnesemia and arrhythmia.MethodsIn this interventional clinical study, 82 patients were randomly assigned to 2 groups. All patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Magnesium deficiency was detected in 7-11% of hospitalized patients, and it was observed that 40% had accompanying hypokalemia, hypophosphothemia, hyponatremia and hypocalcemia (10). Therefore, it may be important to detect hypomagnesemia in the perioperative period in patients with malnutrition, which may lead to significant consequences in anesthesia management (10)(11)(12). Known causes of hypomagnesemia in surgical patients; decreased dietary intake, poor gastrointestinal absorption, increased loss of the gastrointestinal tract, alcoholism, diabetes mellitus and increased renal loss (12).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Magnesium deficiency was detected in 7-11% of hospitalized patients, and it was observed that 40% had accompanying hypokalemia, hypophosphothemia, hyponatremia and hypocalcemia (10). Therefore, it may be important to detect hypomagnesemia in the perioperative period in patients with malnutrition, which may lead to significant consequences in anesthesia management (10)(11)(12). Known causes of hypomagnesemia in surgical patients; decreased dietary intake, poor gastrointestinal absorption, increased loss of the gastrointestinal tract, alcoholism, diabetes mellitus and increased renal loss (12).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it may be important to detect hypomagnesemia in the perioperative period in patients with malnutrition, which may lead to significant consequences in anesthesia management (10)(11)(12). Known causes of hypomagnesemia in surgical patients; decreased dietary intake, poor gastrointestinal absorption, increased loss of the gastrointestinal tract, alcoholism, diabetes mellitus and increased renal loss (12). In addition, it is important to detect it in the perioperative period due to its interaction with agents such as anesthetic agents, diuretics, thiazides, and valproic acid (10).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies evaluated the achievement of stable magnesium levels after bolus intravenous administration, how it is usually used, or followed by continuous infusion that is demonstrated the same effective levels [ 45 ]. The oral route has been suggested in prophylactic therapy to prevent postoperative arrhythmias [ 46 ], but these investigations have aimed at measurement on total magnesium and not ionized bioactive free form [ 47 ].…”
Section: Ionized Vs Total Magnesium Levels In the Perioperative Settingmentioning
confidence: 99%
“…Some studies evaluated the achievement of stable magnesium levels after bolus intravenous administration, how it is usually used, or followed by continuous infusion that is demonstrated the same effective levels [45]. The oral route has been suggested in prophylactic therapy to prevent postoperative arrhythmias [46], but these investigations have aimed at measurement on total magnesium and not ionized bioactive free form [47]. dosages from 50 to 100 mg/kg without reported complications [54], others consider it possibly dangerous and thinking there is not currently licensed for intrathecal administration [55].…”
Section: Ionized Vs Total Magnesium Levels In the Perioperative Settingmentioning
confidence: 99%